Teaching Coupling Mechanisms - A Case Study - Roßmanith, Hans; et al. (EMC 2003 Boston, 2003)
An EMC experiment is described, which demonstrates a combination of ohmic, capacitive and inductive coupling. Based on the test set-up an equivalent circuit is derived, which can be used to analyse and to explain the somewhat unexpected behaviour of the test set-up during the different experiments. These experiments are used as part of an EMC course and the procedure of how to understand the underlying effects will be explained in this paper step by step.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.lselek.teachi
Keywords: Coupling mechanisms; EMC-experiment; Equivalent circuit